CLINICО-MORPHOLOGICAL CHARACTERISTIC OF SQUAMOUS-CELL CARCINOMAS OF LARYNX - Gasyuk, Y.A. (World of Medicine and Biology, 2012)
Аn analysis of literary sources, devoted to the morbidity, etiology, clinical and histological classification of squamous cell carcinoma of larynx is conducted. The basic factors influencing into the regional metastasis and clinical features of carcinoma of this localization are showed. The multifactor grading systems, which are used in the modern oncology for prediction of the clinical course of squamous cell carcinoma of larynx are presented. A review of literature, devoted to the methods of diagnostic and treatment also is conducted. Algorithms of the treatment depending to the primary localization of squamous cell carcinoma of larynx and the stage of process are showed. A comparison of the efficiency of different methods of treatments, including non-traditional modes of fractionation of the dose during distant gamma-therapy is conducted